Analytical mapping of registered criminal activities in Vilnius city - Beconytė, Giedrė; Eismontaitė, Agnė; Romanovas, Denis (Geodesy and Cartography, 2012)
The paper describes the method and the basic results of research into data on criminal activities in Vilnius city. Approximately 100000 incidents registered by police in both 2010 and 2011 have been located and geocoded using their street address information. Analysis of territorial distribution of the incidents in general and of themost common types (assaults, robberies and thefts, motor vehicle thefts and minor offences) in two years reveals that there exist higher concentration areas for all types of crimes. Over one year such areas grew but generally retained their shape and location. The density of incidents is generally dependent on population density, but also tends to concentrate around some shopping centres and entertainment areas. Kernel density spatial analysis method produces visually expressive results and should be applied for fast visual analysis and comparison of data.